2015
DOI: 10.19173/irrodl.v16i2.2010
|View full text |Cite
|
Sign up to set email alerts
|

Coursera’s introductory human physiology course: Factors that characterize successful completion of a MOOC

Abstract: Since Massive Open Online Courses (MOOCs) are accessible by anyone in the world at no cost, they have large enrollments that are conducive to educational research. This study examines students in the Coursera MOOC, Introductory Human Physiology. Of the 33,378 students who accessed the course, around 15,000 students responded to items on the pre-course survey about their age, educational background, proficiency in English, and plans for participating in the course. We categorized students who completed the pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 16 publications
4
47
1
21
Order By: Relevance
“…Nonnative English-speaking students read more slowly than native speakers and are likely to play a video slowly to understand instructors' lessons (Reilly et al, 2016) and may require more time to learn the content, sometimes falling behind (Sanchez-Gordon & Luján-Mora, 2014). Nonnative English-speaking students tend to achieve lower scores than Englishspeaking students in MOOCs (Engle et al, 2015;Reilly et al, 2016) Another concern is nonnative English-speaking learners' participation in social interaction, such as online discussion (Colas et al, 2016). In an analysis of online forum participation in a business course offered in Coursera, Gillani and Eynon (2014) found that European and North American participants not only achieved higher grades in forum participation than those from Asia but were also more visible in online forums, participating in discussions more actively than other participants.…”
Section: Nonnative English-speaking Participants' Learning In Moocsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonnative English-speaking students read more slowly than native speakers and are likely to play a video slowly to understand instructors' lessons (Reilly et al, 2016) and may require more time to learn the content, sometimes falling behind (Sanchez-Gordon & Luján-Mora, 2014). Nonnative English-speaking students tend to achieve lower scores than Englishspeaking students in MOOCs (Engle et al, 2015;Reilly et al, 2016) Another concern is nonnative English-speaking learners' participation in social interaction, such as online discussion (Colas et al, 2016). In an analysis of online forum participation in a business course offered in Coursera, Gillani and Eynon (2014) found that European and North American participants not only achieved higher grades in forum participation than those from Asia but were also more visible in online forums, participating in discussions more actively than other participants.…”
Section: Nonnative English-speaking Participants' Learning In Moocsmentioning
confidence: 99%
“…According to Shah (2015a) Among the growing numbers of MOOC students are nonnative English-speaking learners. Although no official statistical data are available on their numbers, Engle, Mankoff, and Carbrey (2015) examined student characteristics accessed via Introductory Human Physiology, offered through Coursera. Among the 33,378 learners signed up for the MOOC, 15,310 students responded to the survey, 56.9% of whom reported that English was not their first language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Μάλιστα, η ανάπτυξη και η εξέλιξη των MOOCs στο διεθνές εκπαιδευτικό περιβάλλον εμφανίζεται ως καινοτομία που αποκτά ραγδαία εξάπλωση σε παγκόσμιο επίπεδο τόσο στην περιοχή της συμβατικής τριτοβάθμιας εκπαίδευσης όσο και των Ανοικτών Πανεπιστημίων (Baggaley, 2013;Moessinger, 2013;Siemens, 2013;Waldrop, 2013), γεγονός που φανερώνεται και από το μεγάλο αριθμό σχετικών επιστημονικών δημοσιεύσεων (βλ. ενδεικτικά : Chen, 2014;Colvin et al, 2014;Engle, Mankoff, & Carbrey, 2015;Firmin et al, 2014;Hollands & Tirthali, 2014;Liyanagunawardena, Adams, & Williams, 2013;Rodriguez, 2012;Stewart, 2013;Suen, 2014;Xu & Jaggars, 2014). Στόχος της εργασίας αυτής είναι η ανίχνευση των αντιλήψεων των μελών του Διδακτικού Ερευνητικού Προσωπικού (ΔΕΠ) του Ελληνικού Ανοικτού Πανεπιστημίου (ΕΑΠ) για τις δυνατότητες παροχής ανοικτής και εξ αποστάσεως εκπαίδευσης από το ίδρυμα με τη χρήση των MOOCs.…”
Section: εισαγωγήunclassified
“…On the one hand, only a small fraction of all MOOC participants use the forum to communicate (Abnar, Takaffoli, Rabbany, & Zaïane, 2015). However, forum activity often goes along with higher engagement in the course and higher completion rates (Anderson, Huttenlocher, Kleinberg, & Leskovec, 2014;Engle, Mankoff, & Carbrey, 2015). Discussion activities between learners in MOOCs offer the potential of involving more learners in sustainable collaborative knowledge building in a social context when adequately supported (c.f.…”
Section: Introductionmentioning
confidence: 99%